2006
DOI: 10.3748/wjg.v12.i6.974
|View full text |Cite
|
Sign up to set email alerts
|

Subfulminant hepatitis B after infliximab in Crohn’s disease: Need for HBV-screening

Abstract: Infections are a major adverse effect during the treatment with anti-TNF-alpha. While exclusion of any bacterial infection and screening for tuberculosis are mandatory before initiating a therapy with anti-TNF-alpha-antibodies, there are no guidelines whether to screen for or how to deal with chronic viral infections such as hepatitis B. In this case report, we have described a patient with Crohn's disease who developed subfulminant hepatitis B after the fourth infusion of infliximab due to an unrecognized HBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(100 citation statements)
references
References 20 publications
4
93
0
3
Order By: Relevance
“…Neutralization of the TNF receptor during therapy with infliximab for Crohn's disease resulted in (re)activation of HBV among chronic HBV carriers. 31,32 Infliximab has been shown to restore the suppressive capacity of Treg. 19,33 PBMCs from patients with an acute HBV infection produce more TNF-␣ compared with PBMCs from patients with a chronic HBV infection, and a previous study by Van der Molen et al showed that the total amount of TNF-␣ produced by isolated myeloid-derived DC from patients with a chronic HBV infection was decreased compared with myeloidderived DC from healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralization of the TNF receptor during therapy with infliximab for Crohn's disease resulted in (re)activation of HBV among chronic HBV carriers. 31,32 Infliximab has been shown to restore the suppressive capacity of Treg. 19,33 PBMCs from patients with an acute HBV infection produce more TNF-␣ compared with PBMCs from patients with a chronic HBV infection, and a previous study by Van der Molen et al showed that the total amount of TNF-␣ produced by isolated myeloid-derived DC from patients with a chronic HBV infection was decreased compared with myeloidderived DC from healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29][30] Table 3 presents a summary of studies reporting reactivation of HBV after infliximab, specifically in patients with IBD (CD in all cases). 7,[31][32][33][34][35][36][37][38] Cases of reactivation after treatment with infliximab have been described in occult carriers of HBV who are negative for HBsAg and positive for anti-HBc antibody 37 (see occult HBV infection, below). Reactivation of HBV infection in HBsAg carriers occurred as soon as after the HBsAg, hepatitis B surface antigen.…”
Section: Which Ibd Patients Should Be Screened For Prior Hbv ⁄ Hcv Exmentioning
confidence: 99%
“…Among patients who have received immunosuppressants, the rate of liver dysfunction was higher among HBsAg-positive patients than among HBsAgnegative ones (166). HBV reactivation in IBD patients treated with IFX is described in several patients in Table 4 (167)(168)(169)(170)(171)(172)(173)(174).…”
Section: Viral Infections Hepatitis B Virus Reactivationmentioning
confidence: 99%
“…Symptoms of HBV reactivation can include fever, malaise, fatigue, nausea, loss of appetite, weight loss, weakness, dyspepsia, and joint and/or abdominal pain (169,(171)(172)(173). Hepatic manifestations are the predominant symptoms, including hepatitis or jaundice with elevated AST, ALT, alkaline phosphatase (ALP), γ-glutamyl transpeptidase and total bilirubin.…”
Section: Viral Infections Hepatitis B Virus Reactivationmentioning
confidence: 99%
See 1 more Smart Citation